2003
DOI: 10.1046/j.1471-4159.2003.01655.x
|View full text |Cite
|
Sign up to set email alerts
|

The adhesion protein TAG‐1 has a ganglioside environment in the sphingolipid‐enriched membrane domains of neuronal cells in culture

Abstract: We studied the interactions between gangliosides and proteins at the exoplasmic surface of the sphingolipid-enriched membrane domains by ganglioside photolabeling combined with cell surface biotin labeling. After cell photolabeling with radioactive photoactivable derivatives of GM3, GM1 and GD1b gangliosides, followed by cell surface biotin labeling, sphingolipid-enriched domains were prepared and immunoprecipitated with streptavidin-coupled beads, under experimental conditions preserving the integrity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…Sphingosine is very rapidly and extensively taken up by cells, and it is immediately and e‹cient-ly acylated to ceramide, which is then converted into more complex sphingolipids. Under these conditions, in all the cell types so far investigated, all sphingolipids (including ceramide, sphingomyelin, neutral glycolipids and gangliosides), and phosphatidylethanolamine (obtained by recycling of radioactive ethanolamine formed in the catabolism of [1-3 H]sphingosine) were metabolically radiolabeled (56,74,77,(94)(95)(96)(97)(98)(99)(100)(101). The great extent of sphingosine recycling for the biosynthesis of complex sphingolipids allows the incorporation of a large amount of radioactivity into sphingolipids.…”
Section: E Remarks On the Analysis Of Drm Fractionsmentioning
confidence: 99%
“…Sphingosine is very rapidly and extensively taken up by cells, and it is immediately and e‹cient-ly acylated to ceramide, which is then converted into more complex sphingolipids. Under these conditions, in all the cell types so far investigated, all sphingolipids (including ceramide, sphingomyelin, neutral glycolipids and gangliosides), and phosphatidylethanolamine (obtained by recycling of radioactive ethanolamine formed in the catabolism of [1-3 H]sphingosine) were metabolically radiolabeled (56,74,77,(94)(95)(96)(97)(98)(99)(100)(101). The great extent of sphingosine recycling for the biosynthesis of complex sphingolipids allows the incorporation of a large amount of radioactivity into sphingolipids.…”
Section: E Remarks On the Analysis Of Drm Fractionsmentioning
confidence: 99%
“…These domains are involved in the trafficking and sorting of specific proteins, as well as in signal transduction processes (2,3). The lipid domain composition and the machinery of signal transduction were extensively studied in neurons (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In neurons and neuronal cell lines, many lines of evidence suggest that lipid membrane domains or multimolecular complexes localized within such domains are directly involved in the process of neuronal differentiation.…”
mentioning
confidence: 99%
“…Particularly significant seem to be the interactions of sphingolipids with proAbbreviations: BME, basal modified Eagle's medium; HPTLC, high-performance thin-layer chromatography; [1- 2 To whom correspondence should be addressed. e-mail: alessandro.prinetti@unimi.it tein kinases of the Src family, probably the most typical protein family localized in lipid domains, as well as with other proteins implicated in the Src signaling cassette (4,7,(8)(9)(10)(11)(12)(13)(14). Interestingly, the lipid composition changes were accompanied by changes in the association of signaling molecules with the lipid membrane domain during neuronal cell differentiation (9).…”
mentioning
confidence: 99%
“…Photolabeling with photoactivable GM3 provided evidence for the specifi c role of GM3 in reducing insulin receptor-mediated processes in adipocytes ( 13 ) and showed that, following its interaction with CD9, GM3 downregulated tumor cell motility and malignancy ( 14 ). GM1 was found to interact with several membrane and cytosolic proteins (15)(16)(17)(18), two of which were characterized as caveolin-1 ( 16 ) and tubulin ( 17 ), and that GM3, GM1, and GD1b interacted with TAG-1 in the plasma membrane lipid rafts of neuronal cells ( 19,20 ).…”
Section: Synthesis Of 18-amino-octadecanoic Acid (Seementioning
confidence: 99%
“…The presence of Lyn and G ␣ i was assessed by immunoblotting with specifi c antibodies, followed by reaction with secondary HRP-conjugated antibody ( 11,12,15,18,19,27,30,33 ).…”
Section: Analysis Of Protein Patternsmentioning
confidence: 99%